Early Changes in Nitrate Uptake and Assimilation Under Drought in Relation to Transpiration - Gloser, Vít; Dvorackova, Michaela; Mota, Daniel Hernandez; Petrovic, Bojana; Gonzalez, Patricia; Geilfus, Christoph Martin (Frontiers in Plant Science, 2020)
Soil drying combined with nitrogen deficiency poses a grave threat to agricultural crop production. The rate at which nitrate is taken up depends partly on the uptake and transpiration of water. Rapid changes in nitrate assimilation, in contrast to other N forms, may serve as a component of the plant stress response to drought because nitrate assimilation may lead to changes in xylem pH. The modulation of xylem sap pH may be relevant for stomata regulation via the delivery of abscisic acid (ABA) to guard cells. In several factorial experiments, we investigated the interactions between nitrate and water availability on nitrate fate in the plant, as well as their possible implications for the early drought-stress response. We monitored the short-term response (2-6 d) of nitrate in biomass, transport to shoot and reduction in Pisum sativum, Hordeum vulgare, Vicia faba and Nicotiana tabacum and correlated this with sap pH and transpiration rates. Cultivation on inorganic substrate ensured control over nutrient and water supply and prevented nodulation in legume species. NO3− content in biomass decreased in most of the species under drought indicating significant decline in NO3− uptake. H. vulgare had the highest NO3− concentrations in all organs even under drought and low NO3− treatment. This species can likely respond much better to the combined adverse effects of low NO3− and water scarcity. Nitrate reductase activity (NRA) was reduced in both roots and leaves of water deficient plants in all species except H. vulgare, presumably due to its high NO3− contents. Further, transient reduction in NO3− availability had no effect on sap pH. Therefore, it seems unlikely that NRA shifts from shoot root leading to the supposed alkalization of sap. We also did not observe any interactive effects of NO3− and water deficiency on transpiration. Hence, as long as leaf NO3− content remains stable, NO3− availability in soil is not linked to short-term modulation of transpiration.